The This study examines the practice of sapambari in the ijarah (wage contract) system of the Banjar community, where remuneration is not agreed upon in a specific amount at the outset, but rather entrusted to the sincerity of the service user. This practice contrasts with the DSN-MUI Fatwa No. 112/DSN-MUI/IX/2017, which stipulates that the amount or quality of ujrah must be clearly defined in any ijarah contract. The study aims to explore the sociocultural reasons behind the use of sapambari an - Faridah, Faridah; Hasanah, Tuti; Fitriani, Ahda (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
This study examines the practice of sapambari in the ijarah (wage contract) system of the Banjar community, where remuneration is not agreed upon in a specific amount at the outset, but rather entrusted to the sincerity of the service user. This practice contrasts with the DSN-MUI Fatwa No. 112/DSN-MUI/IX/2017, which stipulates that the amount or quality of ujrah must be clearly defined in any ijarah contract. The study aims to explore the sociocultural reasons behind the use of sapambari and evaluate its validity within the framework of Islamic economic law. Employing an empirical legal research method with a descriptive qualitative approach, data were collected through in-depth interviews and document analysis involving 22 informants from the Banjar community. The findings identify four main factors contributing to the practice: (1) the habit of service users not specifying wages at the beginning; (2) the habit of providers not stating the wage amount; (3) the perception that the result of work is a gift rather than compensation; and (4) the influence of Islamic boarding school education. From the perspective of Islamic economic law, the absence of specific ujrah is legitimized through the principle of ‘urf (custom), rendering the ijarah contract with sapambari remuneration legally valid. The study implies the necessity of incorporating cultural practices into the formulation of local Sharia-based legal norms.